PERFORMANCE OF GROWING CALVES FED ON BANANA (MUSA PARADISIACA) STEM - BHIM SEN; SINGH, JAI; VERMA, TARUN; R. PATEL, PRABHAT (The Bioscan, 2014)
The present work is planned with an aim to evaluate the chemical composition of the banana stem and its nutritional potential as non-conventional feed resource on cross-bred calves. Performance of 16 growing cross bred (Sahiwal × Jersey) male calves at one and half year of age having average body weight of 353.35 ± 6.50 kg were equally divided into 4 groups. The animals were fed concentrate mixture alongwith wheat bhusa and chaffed dried banana (Musa paradisiaca) stem in the ratio of 100:0, 90:10, 80:20 and 60:40 in groups I, II, III and IV, respectively. The feed intake (80.04 g/w0.75), digestibility of DM (57.32%), biological value (78.02%), gain in body weight (312.49g/head/day) and nutrients balance were apparently higher in group II than rest of the groups. The per cent digestibility coefficient of OM (57.27), CP (58.47), EE (57.38), CF (56.92), NFE (56.25) and TCHO (56.80) were significantly (p <0.05) higher in group II than the control. The feed cost/100g body weight gain was the lowest in group II (Rs. 2.67). Upto 10% Banana stem can be included in ruminant ration without any anti effect on the body.